Pengembangan Spiritualitas Siswa melalui Layanan Bimbingan Rohani Islam dengan Metode Ceramah - Putri, Shaula Astika; Al Wafi, Salma Rasyida Al Wafi; Azizah, Nur (Institut Agama Islam Negeri Parepare, 2023)
The research aims to describe how to develop students' spirituality through Islamic spiritual guidance services using the lecture method. This type of research is qualitative research. The data source for this research is the observation of researchers at SMA Negeri 4 Purwokerto. In contrast, the research subjects were female students of SMA Negeri 4 Purwokerto who were Muslim. Observation and documentation data collection methods. The method used is Participatory Action Research (PAR), carried out in five stages: problem identification, action planning, action taking, evaluation, and reflection. The results of the study state that students need spiritual guidance services. The implementation of spiritual guidance services is to use the lecture method, which is suitable, efficient, and effective for schools. These efforts are made to develop their relationship with Allah SWT. Not only can counseling teachers provide spiritual guidance services to students, but teachers in schools can also provide spiritual guidance services